Kajian Efikasi dan Keamanan Terapi Antikoagulan Baru pada Pasien Deep Vein Thrombosis - Ridwan Rasyid; Pringgodigdo Nugroho; Yoga Yuniadi (Jurnal Kardiologi Indonesia, 2012)
Background. Warfarin is a standard medication for deep vein thrombosis (DVT). However, there are some limitations of its use due to the need of regular monitoring and problems of drug to drug and drug to food interactions. Newer  oral anticoagulants (NOAC) is being considered as substitution to warfarin, yet they need some evidences on its safety and efficacy. This evidence case report is aimed to elaborate safety and efficacy of NOAC (dabigatran and rivaroxaban) in the setting of DVT.Methods  and Results.  Relevant articles are searched in Pubmed and Proquest database. Only recent article which less than 5 year publication included in this study. RE-COVER  study showed  non-inferiority of dabigatran as compare to warfarin in treating DVT patients. Mortality rate and recurrent rate of DVT were 2.4% vs. 2.1% in dabigatran and warfarin respectively (HR=1,10 CI 95%  = 0,65-1,84). Dabigatran showed less bleeding rate compare to warfarin, 5.6% vs. 8.8% respectively (HR = 0,63CI95% = 0,47 - 0,84; RRR =29%, p = 0,0002). Similar results is shown in EINSTEIN study that compares rivaroxaban with warfarin. Mortality rate and recurrent rate of DVT were 2.1% vs. 3% in rivaroxaban and warfarin respectively (HR=0,68  CI 95% = 0,44-1,04). Total bleeding rate were7.3% vs. 7% and major bleeding were 0.8% vs. 1.2% in rivaroxaban and warfarin respectively.Conclusion. Both dabigatran and rivaroxaban showed non inferior efficacy as compare to warfarin in the treatment of DVT, and slightly better bleeding rate.